Malaria parasitaemia among the under-12 children in Akure, Ondo State, Nigeria - Oluwafemi, Rosena O.; Afolabi, Olajide J.; Oluwafemi, Toluwani M.; Momoh, Abdul O.; Oniya, Mobolanle O. (International Journal of Research in Medical Sciences, 2025)
Background: Malaria is a preventable and curable but life-threatening disease that is transmitted to humans by female Anophelis mosquitoes. It is mostly found in tropical countries. The study sets out to determine the malaria parasitaemia among children under the age of 12 years in Akure, Ondo State. Methods: The study was a prospective, cross sectional and hospital-based where blood specimen were collected from children aged 1 day old to 12 years. Microscopy method was used to detect the malaria parasite and confirmed by nested PCR method. The data obtained were subjected to statistical analysis using Microsoft excel and the statistical package for the social sciences (SPSS) version 20.0 Results: Overall prevalence of malaria was 64.2%. The neonates had the highest prevalence of 96.8%. P. falciparum was the most predominant species (99.4%), prevalence of malaria decreases with increasing birth order but prevalence was significantly higher among children in the first birth order and lower socio-economic class. There was no significant difference between parasite intensity among gender, p=0.585. Majority of children (94.2%) were well nourished. Conclusions: The study showed that prevalence of malaria is high in children under 12 in Ondo State. The neonates were worse hit, though with least parasite intensity. We suggest intensified and concerted effort in malaria prevention and control in the state.